Evaluation of Acetylcholine Release and Hold Electrochemical Device by CCD Type Ion Image Sensor. (16th August 2016) - Kageyama, Itsuki; Kato, Ryo; Sawada, Kazuaki; Hattori, Toshiaki
Abstract : Acetylcholine (ACh) is well known as one of the important neurotransmitters. Imaging the dynamics of ACh in realtime is essential for the understanding of neuronal communication. The meaningful observation of living cells requires also developments of tools to manipulate cells and to add stimuli, not only development of the imaging method. As a method of local chemical stimulation, in this study, we developed an ACh release and hold electrochemical device. The device consists of three layers; PVC membrane including ACh and tetrakis[3, 5-bis(trifluoromethyl)pheny]borate (TFPB), poly(3, 4-ethylenedioxy thiophen) (PEDOT) layer, and a glassy carbon electrode. The device was characterized by cyclic voltammetry. Amount of ACh released from the device applied at constant potential was monitored by CCD type ACh image sensors. It was demonstrated that the device can release and hold of ACh, and the device can be recharged by application of negative potential.